The Effect of Using Black Box Ai to Improve Web Programming Skills of Informatics Education Students - Banung, Floriana Letni; Sogen, Maria Magdalena Beatrice; Ndao, Angelo Fransisco Daga; Tunu, Sherwin Gainell; Koa, Ayu Desita (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Student often face challenges or difficulties in creating attra web interfaces,particularly in understanding code and finding suitable coding references. This study aims to determine the impact of using Blackbox.AI in supporting seventh-semester students of the informatics Education study program at Universitas Citra Bangsa in enahancing their web programming skills approach with data collected were conducted using observation sheets to directly monitor the students’ skill development in independently completing web programming projects. The coolected data were analyzed using descriptive statistics and significance testing. The results of the study indicate that the use of Blackbox.AI has a positive and significant impact on improving students’ web programming skills. Students found it easier to search for coding references, produced more attractive web designs, and developed better-structured layouts. Furthermore , students expressed high satisfaction with the outcomes of their proggramming tasks. Based on the questionnaire results, the majority of students stated that the use of Blackbox.AI greatly assisted them in understanding both the concepts and practices of web programming.